2021
DOI: 10.1159/000514953
|View full text |Cite
|
Sign up to set email alerts
|

NASH/Liver Fibrosis Prevalence and Incidence of Nonliver Comorbidities among People with NAFLD and Incidence of NAFLD by Metabolic Comorbidities: Lessons from South Korea

Abstract: Background: NAFLD incidence, NASH prevalence, NAFLD fibrosis prevalence, incidence of metabolic comorbidities, as well as mortality data in the NAFLD population remain limited. Aims: We used a meta-analytic approach to “stage” NAFLD among the Korean population. Methods: We searched PubMed, Embase, Cochrane Library, and KoreaMed from inception until June 29, 2019 and calculated pooled estimates via random-effects model. Results: We screened 1,485 studies and analyzed 191 eligible studies: 179 (3,556,579 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 36 publications
2
51
0
2
Order By: Relevance
“…17 In a meta-analysis of Korean studies, the prevalence of diabetes in patients with NAFLD was 14.2%, higher than the 5.2% of the control group. 83 The results of a meta-analysis of other studies also showed an increase of about 2.2 times in the incidence of T2DM. 84…”
Section: -4-1 Cardiovascular Diseasementioning
confidence: 92%
See 3 more Smart Citations
“…17 In a meta-analysis of Korean studies, the prevalence of diabetes in patients with NAFLD was 14.2%, higher than the 5.2% of the control group. 83 The results of a meta-analysis of other studies also showed an increase of about 2.2 times in the incidence of T2DM. 84…”
Section: -4-1 Cardiovascular Diseasementioning
confidence: 92%
“…85 In a meta-analysis of Korean studies, the incidence of metabolic syndrome was 40.7% in patients with NAFLD and 11.2% in the control group. 83…”
Section: -4-3 Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…As the Westernized lifestyle and the rate of receiving health screenings have increased, the recent prevalence of NAFLD in Korea has also increased. The prevalence of NAFLD is estimated to be over 30% in Korea [ 10 ]. NAFLD ranges from simple liver steatosis to steatohepatitis, and it can progress to liver cirrhosis and liver failure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%